2020
DOI: 10.5194/bg-17-3705-2020
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of seasonal- and event-scale DOC dynamics at the outlet of mountainous peatlands revealed by high-frequency monitoring

Abstract: Abstract. Peatlands store ∼ 20 %–30 % of the global soil organic carbon stock and are an important source of dissolved organic carbon (DOC) for inland waters. Recent improvements for in situ optical monitoring revealed that the DOC concentration in streams draining peatlands is highly variable, showing seasonal variation and short and intense DOC concentration peaks. This study aimed to statistically determine the variables driving stream DOC concentration variations at seasonal and event scales. Two mountaino… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 96 publications
0
9
0
Order By: Relevance
“…Pulses of DOC during flood events can be understood as a succession of hydrological connection and disconnection between the peatland and the stream, causing changes in DOC concentrations in the stream (Billett et al, 2006;Laudon et al, 2011; Jutebring Sterte et al, 2022). The runoff generation into the peat is controlled by the water table depth (WTD; Holden and Burt, 2003;Frei et al, 2010), where a large WTD increase during flood events leads to hydrological reconnection between DOC sources (Inamdar et al, 2004;Tunaley et al, 2016;Rosset et al, 2020) and greater DOC exports (Blaurock et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pulses of DOC during flood events can be understood as a succession of hydrological connection and disconnection between the peatland and the stream, causing changes in DOC concentrations in the stream (Billett et al, 2006;Laudon et al, 2011; Jutebring Sterte et al, 2022). The runoff generation into the peat is controlled by the water table depth (WTD; Holden and Burt, 2003;Frei et al, 2010), where a large WTD increase during flood events leads to hydrological reconnection between DOC sources (Inamdar et al, 2004;Tunaley et al, 2016;Rosset et al, 2020) and greater DOC exports (Blaurock et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…DOC exports during flood events may vary depending on many parameters: the magnitude of the rainfall events, the season and the porewater temperature, the recurrence of high-flow events, the presence of a free-rainfall period, and the antecedent wetness of the catchment (Leach et al, 2016;Tiwari et al, 2018;Rosset et al, 2020;Blaurock et al, 2021). Previous studies have highlighted that long periods between rainfall events favour DOC production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data can be deposited in another data repository with the reference to the article. The SNO Tourbières dataset will mention if it contains this particular sub-dataset: 'HasPart' (e.g., Rosset, 2019b;.…”
Section: Involvement Of the Si Sno Tourbières In National And International Research Infrastructuresmentioning
confidence: 99%
“…The rising organic carbon concentration tends to coincide with iron increases, and this phenomenon may be linked to the declining sulfur deposition (Björnerås et al, 2017). Additionally, seasonal variations of DOC concentration and transportation are highly driven by water temperature (Rosset et al, 2020). For example, Egea et al (2019) found that water temperatures positively affected DOC transportation.…”
Section: Introductionmentioning
confidence: 99%